RELIGIOUS-EDUCATIONAL BASES FOR PREVENTING FAMILY DISPUTES - Jumaniyazova Mokhira (Web of Journals Publishing, 2024)
This article focuses on the negative impact of various forms of violence and oppression against women and children in the family and society, which are becoming more relevant in the world, especially in our country, on our national spirituality, and the reforms implemented by our country in this regard. In particular, a detailed analysis of the meaning of the verses and hadīths about the importance of women in the family, what should be given importance in the upbringing of children in the religion of Islām, is given. Several literatures related to the topic were widely used in the research work. The main purpose of the article is to draw attention to the importance of Islām and its advice and wisdom in preventing violence against women and children in the family. Therefore, explaining the peculiarities of our religious values is one of the best solutions to prevent violence against women and children. Especially, analyzing it from a scientific and theoretical point of view will help to understand its deeper content, and this is what the research focuses on. In particular, it is noteworthy that through the verses and wisdoms of the Holy Qur'an and Hadīths, the high attention paid to women and kindness in raising children are among the human qualities. This is an important basis for our ability to resist various foreign ideas. In addition, attention is also paid to a brief analysis of scientific concepts related to the topic. It is aimed to increase the scientific weight of the topic. The above issues are researched in the scientific article.
Keywords: Family relations, physical violence against women and children, national and religious values, Islāmic enlightenment, child upbringing, Moral views, regulatory and legal documents, international documents